Linear regression : a mathematical introduction - Gujarati, Damodar N. (Los Angeles, CA : SAGE Publications, Inc, 2019)
Damodar N. Gujarati's Linear Regression: A Mathematical Introduction presents linear regression theory in a rigorous, but approachable manner that is accessible to students in all social sciences. This concise title goes step-by-step through the intricacies, and theory and practice of regression analysis. The technical discussion is provided in a clear style that doesn't overwhelm the reader with abstract mathematics. End-of-chapter exercises test mastery of the content and advanced discussion of some of the topics is offered in the appendices.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Regression analysis; Regression analysis -- Data processing